TANGGUNG JAWAB PERANGKAT DESA DALAM PELAKSANAAN PENDIDIKAN NON FORMAL DI KELURAHAN TEMBILAHAN KOTA KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - wahyuni, Try; Natuna, Daeng Ayub; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Responsibility is human awareness of intentional and intentional acts and intentional actions. The purpose of this study is to find out how high the responsibility of village officials in implementing non-formal education in Kelurahan Tembilahan Kota Kecamatan Tembilahan Kabupaten Indragiri Hilir and know how much the contribution of the responsibility of the apparatus villages in the implementation of non formal education in Kelurahan Tembilahan Kota Kecamatan Tembilahan Kabupaten Indragiri Hilir. This study consists of 1 variable, consisting of 5 indicators. The population in this study were 144. The sample in this study used the Simple Random Sampling Technique, which is sampling from the population carried out randomly without regard to strata in the population, this way is done when members of the population are considered homogeneous (Sugiyono, 2011: 57). The instrument in this study was a questionnaire which amounted to 45 statements about responsibility consisting of 5 indicators. The sample in this study amounted to 92. Based on the average results of the mean value for the responsibilities of village officials in the implementation of non-formal education in Kelurahan Tembilahan Kota Kecamatan Tembilahan Kabupaten Indragiri Hilir is relatively high, with a mean of 4.33 and a standard deviation of 0.31. The interpretation obtained for each indicator of the responsibility of the village apparatus in the implementation of non-formal education in Kelurahan Tembilahan Kota Kecamatan Tembilahan Kabupaten Indragiri Hilir is all classified as high. So, seen the most dominant of these 5 indicators is the responsibility towards the family. Key Words: Responsibility, Village Officials, Non-Formal Education